PERAN KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN PROFESIONALITAS GURU - Nia Sari; Hamenkubuwono Hamengkubuwono; Saidil Mustar (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2020)
This study aimed to find out a depiction of Madrasah principal’s roles in an effort to improve teachers’ professionalism at MIN 1 Rejang Lebong, Bengkulu. This study used a qualitative approach. The data were collected using observation and interviews, and they were analyzed using the approach of Miles et al, namely data reduction, data presentation and conclusion drawing. This study concluded that the principal's managerial roles in improving teachers’ professionalism were: assigning tasks to teachers according to their expertise, conducting coaching and training, and inviting teachers to join the Ibtidaiyah Madrasah Teacher Working Group (in Indonesian abbreviation, KKGMI) of Rejang Lebong Regency.Keywords: Leadership, Principal, Teachers’ professionalism